UNTAGGED MUTATION IN RICE GAL4/VP16 TRANSCRIPTIONAL ACTIVATOR FACILITATED-ENHANCER TRAP LINES - Sri Koerniati (Indonesian Agency for Agricultural Research and Development, 2013)
An enhancer trap system is an insertional mutagenesis based upon gene expression, instead of gene knock-out, so its insertion in genome is expected not linked to any dramatic changes in plant phenotypes. Gene knock-out, leading to lossof- function (LoF) mutation, is a dominant approach for rice functional genomic studies. The objective of this study was to find out whether Transcriptional Activator-Facilitated Enhancer Trap (TAFET) T-DNA insertion inducing mutant phenotypes in rice TAFET population. Materials used in this experiment were T1 generation of 270 rice TAFET lines. Eight plants of each were grown in the greenhouse and observed for any mutant phenotypes. Phenotypic, histochemical, Southernblot analyses were carried out to define a mutant of pSKC66.1- 8e. Result showed that about 10% of the 270 lines produced chlorophyll-deficient leaves, ranged from yellowish green (viridis), white stripe green zebra-like stripe) to completely white (albino). Albino plants died after two weeks, whilst white stripe or viridis mutants became normal in the next generation(T2). Another mutant was pSKC66.1-8e line which had floral dramatic phenotype change with various spikelet shapes and number of organs, and had a single twisted culm. The flower of mutant also had gus gene expression. Plants with wild type did not express gus gene and had six or more straight culms. Molecular, histochemical and phenotypic analyses of this particular line for three generations indicated that mutant phenotype was not due to the T-DNA insertion. Since there was approved that Tos17 is activated during tissue culture and induced mutant phenotype, this line might relate to Tos17 insertion, but it needs further investigation to gain such conclusion.